Avoidable burden of stomach cancer and potential gains in healthy life years from gradual reductions in salt consumption in Vietnam, 2019-2030: a modelling study - Leopold Ndemnge Aminde; Linda J Cobiac; Dung Phung; Hai N Phung; J Lennert Veerman (Cambridge University Press, 2023)
Abstract Objective: Excess salt consumption is causally linked with stomach cancer, and salt intake among adults in Vietnam is about twice the recommended levels. The aim of this study was to quantify the future burden of stomach cancer that could be avoided from population-wide salt reduction in Vietnam. Design: A dynamic simulation model was developed to quantify the impacts of achieving the 2018 National Vietnam Health Program (8 g/d by 2025 and 7 g/d by 2030) and the WHO (5 g/d) salt reduction policy targets. Data on salt consumption were obtained from the Vietnam 2015 WHO STEPS survey. Health outcomes were estimated over 6-year (2019-2025), 11-year (2019-2030) and lifetime horizons. We conducted one-way and probabilistic sensitivity analyses. Setting: Vietnam. Participants: All adults aged ≥ 25 years (61 million people, 48·4 % men) alive in 2019. Results: Achieving the 2025 and 2030 national salt targets could result in 3400 and 7200 fewer incident cases of stomach cancer, respectively, and avert 1900 and 4800 stomach cancer deaths, respectively. Achieving the WHO target by 2030 could prevent 8400 incident cases and 5900 deaths from stomach cancer. Over the lifespan, this translated to 344 660 (8 g/d), 411 060 (7 g/d) and 493 633 (5 g/d) health-adjusted life years gained, respectively. Conclusions: A sizeable burden of stomach cancer could be avoided, with gains in healthy life years if national and WHO salt targets were attained. Our findings provide impetus for policy makers in Vietnam and Asia to intensify salt reduction strategies to combat stomach cancer and mitigate pressure on the health systems.